Six new species of Heteropriapulus (Monogenea: Dactylogyridae) from South American fishes with an amended diagnosis to the genus - Acosta, Aline Angelina [UNESP]; Franceschini, Lidiane [UNESP]; Zago, Aline Cristina [UNESP]; Scholz, Tomáš; Da Silva, Reinaldo José [UNESP] (Magnolia Press, 2017)
Heteropriapulus Kritsky, 2007 (Monogenea: Dactylogyridae), which originally included only two species from the gills of loricariid catfishes, is reviewed and six newly described species from loricariids in the Paraná River basin in Brazil are added. Diagnosis of the genus is amended and a key to the species identification is provided. Heteropriapulus anchora-diatus n. sp. from Pterygoplichthys ambrosettii (Holmberg) (Hypostominae) differs from its congeners by having a long sclerotized vagina, ventral anchors with short shaft and conspicuous superficial root, and a conspicuous and robust poste-ro-medial process on the dorsal bar; H. bitomus n. sp. from the same fish host differs by the presence of two pairs of scle-rotized patches associated with the ventral anchors; H. falxus n. sp. from Hypostomus strigaticeps (Regan) (Hypostominae) and Hypostomus ancistroides (Ihering) (Hypostominae) is unique by the shape of the accessory piece composed of two strongly sclerotized subunits; H. microcleithrus n. sp. from P. ambrosettii differs by presenting the smallest length of the dorsal bar and unique shape of the longer subunit of the accessory piece resembling the 'hammer and sickle' shape; H. pterygoplichthyi n. sp. from the same host presents unique shape of the longer subunit of the acces-sory piece of the cirrus, which is represented by 'two sickles' jointed by the base; and H. semitortus n. sp. from Rhinelepis aspera Spix & Agassiz (Rhinelepinae) can be distinguished by the accessory piece composed of a single straight unit and a cirrus tube with the highest number of spiral rings at the proximal end (21/2). First molecular data for this genus (partial sequences of the 28S rRNA gene) are provided including the type species H. heterotylus (Jogunoori, Kritsky & Venka-tanarasaiah, 2004).
Keywords: Ectoparasites; Hypostominae; Loricariidae; Neotropical region; Rhinelepinae; Upper Paraná River